2000
DOI: 10.1074/jbc.m006393200
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Properties of Sphingosine 1-Phosphate in Human Hepatic Myofibroblasts

Abstract: Proliferation of hepatic myofibroblasts (hMF) is central for the development of fibrosis during liver injury, and factors that may limit their growth are potential antifibrotic agents. Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid with growth-regulating properties, either via Edg receptors or through intracellular actions. In this study, we examined the effects of S1P on the proliferation of human hMF. Human hMF expressed mRNAs for the S1P receptors Edg1, Edg3, and Edg5. These receptors were functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
92
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 39 publications
11
92
0
Order By: Relevance
“…We previously identified S1P receptors (Edg-1, -3, and -5) in human hepatic myofibroblasts and noted that they relay the antiproliferative effect of S1P (13). In the present study, we show that S1P modulates apoptosis of hepatic myofibroblasts with a dual effect.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…We previously identified S1P receptors (Edg-1, -3, and -5) in human hepatic myofibroblasts and noted that they relay the antiproliferative effect of S1P (13). In the present study, we show that S1P modulates apoptosis of hepatic myofibroblasts with a dual effect.…”
supporting
confidence: 68%
“…S1P is a downstream metabolite of ceramide that is produced after phosphorylation of sphingosine by sphingosine kinase (10). In contrast to ceramide and sphingosine, S1P generally elicits mitogenic and antiapoptotic effects (12), although growth-inhibitory and apoptotic effects have occasionally been described (13)(14)(15)(16)(17)(18). S1P modulates cell function by two distinct mechanisms, either as an intracellular messenger or as a ligand of a family of G proteincoupled receptors, the Edg (endothelial differentiation gene) receptors, which includes Edg-1, -3, -5, -6, and -8 (10,19).…”
mentioning
confidence: 99%
“…Sphingosine kinase (SphK) catalyzes the phosphorylation of sphingosine to sphingosine 1-phosphate, and this metabolite promotes liver fibrogenesis. 10,11 SphK1 is also involved in the regulation of tissue inhibitor of metalloproteinase 1 (TIMP-1) in fibroblasts. 12 TIMP-1 inhibits MMP-9 and MMP-2.…”
mentioning
confidence: 99%
“…It has been shown recently that the LPA counterpart sphin-gosine-1-phosphate (S1P) induced proliferation of hepatic stellate cells (23,48). Other authors reported growth inhibition by S1P in hepatic myofibroblasts (11) and in primary rat hepatocytes stimulated with hepatocyte growth factor (24). On the other hand, LPA was shown to increase motility and migration of a human hepatoma cell line (37).…”
mentioning
confidence: 99%